Kepemimpinan Kepala Sekolah Meningkatkan Mutu Peserta Didik: Analisis Model dan Strategi Pencapaian - Roja, Anfaur; Salim, Hakimuddin (Sekolah Tinggi Agama Islam Sumatera Medan, 2023)
Principal leadership is an effort to influence the situation, conditions and behavior in the school to move the roots in a school to work well together and to achieve a desired goal with the vision and mission of the school. The principal's leadership role in building quality learners is a very real pride for the community as a measure of success in fostering schools. However, in the application of leadership, there are not a few problems faced. This study aims to analyze the principal's leadership models and strategies in improving the quality of students. This research uses descriptive qualitative research, which was conducted at SMK Nusaputera 2 Semarang. Data collection using observation, interviews and documentation studies. The results showed that the leadership model used is a transformative model, which aims to inspire and guide learners to reach their best potential and achieve extraordinary goals. The principal's strategy is very important to participate in building quality learners by participating in realizing the school's vision and mission. The findings in this study are the optimal motivation of the principal to achieve the desired goals. Not only that, the development of the school environment and culture is also a strategy to improve the quality of students.